Unraveling the Effects of Lax Enforcement of Sexual Harassment Policy at Islamic Boarding Schools in West Java, Indonesia - Firdaus, Dwi Rini Sovia; Aminuddin, Ahsani Taqwim; Alamsyah, Feri Ferdinan; Sariswara, Valianty; Soleha, Nadia Ismi (UNIVERSITAS PAKUAN, 2025)
This study investigates the effects of lax enforcement of sexual harassment policies in Islamic boarding schools (pesantren). It analyzes how inadequate disciplinary measures impact victims, the educational environment, and community perceptions. Through a mixed method, including surveys, in-depth interviews, and field observations, this study aims to shed light on the urgency for robust policies and effective enforcement to ensure the safety and well-being of students. This paper explores how pesantren in West Java, Indonesia, actively challenge stereotypes linking religious institutions to sexual harassment. Often mischaracterized as patriarchal and resistant to addressing social issues, pesantren refute these perceptions by fostering environments rooted in Islamic values of dignity, respect, and ethical conduct. Pesantrens shape society's moral, ethical, and spiritual values. However, cases of sexual harassment and weak enforcement of related policies have raised serious concerns about the integrity of these institutions. This study examines the social, psychological, and institutional impacts of inadequate disciplinary measures on victims, perpetrators, and the pesantren community. The findings reveal how lenient sanctions perpetuate a culture of impunity, erode trust, and undermine the moral authority of pesantrens, calling for immediate reforms aligned with Islamic and human rights principles.